1997
DOI: 10.1086/517301
|View full text |Cite
|
Sign up to set email alerts
|

Late Cytomegalovirus Disease in Marrow Transplantation Is Predicted by Virus Load in Plasma

Abstract: Late occurrence of cytomegalovirus (CMV) disease after day 100 after bone marrow transplantation has become an increasing problem; whether a quantitative measurement of CMV DNA in plasma by polymerase chain reaction (P-PCR) could be predictive of such disease was investigated. In a prospective study, 117 subjects undergoing allogeneic marrow transplantation were followed for 120 days with weekly CMV blood cultures, with day 35 bronchoalveolar lavage CMV cultures, with weekly CMV P-PCR, and with clinical follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 15 publications
4
59
0
1
Order By: Relevance
“…In addition, the semiquantitative PCR of plasma has been previously shown to correlate with the risk of CMV diseases. 7 We do agree with the results reported by Butt and Clark, showing a high frequency of positive surveillance results in low-risk patients, and support the necessity of CMV surveillance. Butt and Clark 1 conclusively recommended the use of CMV antigenemia to monitor CMV infection in lowrisk patients as their results showed a low incidence of CMV disease in spite of the high incidence of CMV infec-tion detected by PCR.…”
supporting
confidence: 92%
“…In addition, the semiquantitative PCR of plasma has been previously shown to correlate with the risk of CMV diseases. 7 We do agree with the results reported by Butt and Clark, showing a high frequency of positive surveillance results in low-risk patients, and support the necessity of CMV surveillance. Butt and Clark 1 conclusively recommended the use of CMV antigenemia to monitor CMV infection in lowrisk patients as their results showed a low incidence of CMV disease in spite of the high incidence of CMV infec-tion detected by PCR.…”
supporting
confidence: 92%
“…[36][37][38] However, recent reports have indicated that most of CMV diseases now develop in the late-recovery phase. 34,35,39 All but one patient in our data had chronic GvHD, an established risk factor for the late CMV disease. We thought that continuous screening of antigenemia should be carried out on patients with a preceding episode of positive result and chronic GvHD.…”
Section: Discussionmentioning
confidence: 68%
“…[3][4][5][6]8 These data suggest that the extended AG surveillance performed in our study, may have played an important role in preventing the development of late CMV disease.…”
Section: Discussionmentioning
confidence: 84%
“…[1][2][3] Both strategies focused on the first 100 days after transplantation and after that most of the published series have screened for CMV infection or disease only in the presence of symptoms. [3][4][5][6][7] Therefore, few surveillance data are available on the occurrence of CMV infection and recurrences after day +100. 8 However, some reports have suggested that the prolonged use of ganciclovir may inhibit the development of CMV-specific T cell responses promoting the occurrence of CMV infection and disease after discontinuation of antiviral therapy.…”
mentioning
confidence: 99%